Single cell transcriptional diversity and intercellular crosstalk of human liver cancer - Meng, Yan; Sang, Yan; Liao, Jianping; Zhao, Qiudong; Qu, Shuping; Li, Rong; Jiang, Jinghua; Wang, Meifeng; Wang, Jiahong; Wu, Dong; Cheng, Chun; Wei, Lixin (Cell death & disease, 2022)
Liver cancer arises from the evolutionary selection of the dynamic tumor microenvironment (TME), in which the tumor cell generally becomes more heterogeneous; however, the mechanisms of TME-mediated transcriptional diversity of liver cancer remain unclear. Here, we assess transcriptional diversity in 15 liver cancer patients by single-cell transcriptome analysis and observe transcriptional diversity of tumor cells is associated with stemness in liver cancer patients. Tumor-associated fibroblast (TAF), as a potential driving force behind the heterogeneity in tumor cells within and between tumors, was predicted to interact with high heterogeneous tumor cells via COL1A1-ITGA2. Moreover, COL1A1-mediated YAP-signaling activation might be the mechanistic link between TAF and tumor cells with increased transcriptional diversity. Strikingly, the levels of COL1A1, ITGA2, and YAP are associated with morphological heterogeneity and poor overall survival of liver cancer patients. Beyond providing a potential mechanistic link between the TME and heterogeneous tumor cells, this study establishes that collagen-stimulated YAP activation is associates with transcriptional diversity in tumor cells by upregulating stemness, providing a theoretical basis for individualized treatment targets.